UPAYA PENGEMBANGAN GREEN PORT MELALUI PENGGANTIAN CAPTIVE POWER PADA GANTRY JIB CRANE - Rahman Azis Prasojo; Epiwardi Epiwardi; Gatot Joelianto (SENTIA 2015, 2015)
Port of Panjang is located in Bandar Lampung, Lampung Province. As a strategic port in Indonesia, it requires the development of facilities and equipment to increase its functional role and meets the high standard of service. Four units of Gantry Jib Crane (GJC) in the Dock D is using on-board engine (diesel genset) as a captive power as power supply. Diesel genset operation cost much and poluuting the air around the port.In effort to reach the category of Green Port, PT. Pelindo II intends to save energy and reduce air pollution in the port of panjang, replacing captive power of GJC, which has been using a captive power supply, will be replaced with electricity from the PLN grid. Diesel-gensets that already exist are used as stand-by unit to be operated when the power source of the electricity out or disrupted.The captive power replacement designed and then operating cost analysis and environmental analysis are calculated. With maintaining the genset on each crane, the crane reliability level in the services, loading and unloading can take place continuously.